Cultivating Democracy : Civic Environments and Political Socialization in America - Gimpel, James G. (Book collections on Project MUSE., 2003)
"The authors gathered data on adolescent attitudes by interviewing students in a wide variety of locations, from Baltimore's inner city and suburbs to the most affluent communities in Montgomery County, Maryland. Focusing initially on attitudes toward ethnic diversity and immigration, the authors expanded their focus to the political socialization of young people, including patriotism and political knowledge and participation." "The authors demonstrate how political socialization is shaped through the social messages presented to citizens by others. According to Gimpel, Lay, and Schuknecht, while formal education as a means of socializing youth is critically important, other useful means for communicating positive socializing messages, through political parties, elections, and the media, have been ignored. They recommend compensatory strategies to promote civic engagement among those who are at risk of becoming nonparticipants."--Jacket